HIERARKI STATUS SOSIAL KOLONIAL DALAM NOVEL PANGERAN DARI TIMUR: PERSPEKTIF PASCAKOLONIAL ANIA LOOMBA - Matta, Angellika; Abidin, Aslan; Ridwan, Ridwan (Fakultas Bahasa dan Sastra Indoensia, 2026)
This study aims to examine the differences in social status between the natives and the colonizers in the novel Pangeran dari Timur (Prince of the East) by Iksaka Banu and Kurnia Effendi using Ania Loomba's postcolonial perspective. This study uses a qualitative method with a descriptive-analytical approach. The data sources are quotations from the novel that represent colonial relations, including dialogues, narratives, and scene descriptions. The data were collected through reading and note-taking techniques, then analyzed using the concepts of racial hierarchy, social class, education, and modernity. The results of the study show that colonialism constructed a social status hierarchy that placed European colonizers as the superior group and indigenous people as the inferior group. Education and modernity functioned as means of ideological domination that limited social mobility. The conclusion of the study confirms that colonialism normalized the domination of the colonizers and degraded the dignity of the indigenous people.